Pengaruh Fluktuasi Harga Emas terhadap Keputusan Nasabah Bertransaksi di Pegadaian : (Studi Kasus Pegadaian Simpang Empat) - Hayati Hayati; Fawza Rahmat; Yossi Eriawati (Transformasi: Journal of Economics and Business Management, 2024)
This research is motivated by the influence of gold price fluctuations on customer decisions to transact at Pegadaian (Case Study of Simpang Empat Pegadaian). With the aim of knowing how influential gold price fluctuations are on customer decisions to transact at Simpang Empat Pawnshop. This research uses quantitative methods. The population in this study were Simpang Empat Pawnshop customers. The data collection technique used was by filling out a questionnaire distributed to 91 customers who were sampled. The data used were obtained from primary data and secondary data. The data analysis technique uses simple linear regression analysis. From the test conducted, H0 is rejected while H1 is accepted with an F table value of 12.954 (f count 12.954> f table 3.947) and a significant level of 0.00. This shows that there is a positive and significant effect of the gold price fluctuation variable (X) on customer transaction decisions (Y) Simpang Empat Branch Pawnshop. It can be concluded that the results of this study are in line with previous research, proving that the variable influence of gold price fluctuations has a positive and significant effect on the variable customer transaction decisions at Pegdaian (Case Study of Simpang Empat Pegadaian). What distinguishes it from previous research or previous researchers is the year of research, several data processing methods and the place of research. For the Simpang Empat Pegadaian institution, as an institution that operates in the field of pawnshop services, which cannot be separated from the financial system, of course this research will be very helpful for developing quality and as a reference for becoming a better institution and making customer decisions to transact at Simpang Empat Pegadaian is the right decision.